Nutritional Contents and Bioactive Compounds among Several Variants of Dolichos lablab: Fundamental Facts for Functional Food Development - Elly Purwanti; Feri Eko Hermanto; Wahyu Prihanta; Tutut Indria Permana; I Gusti Ngurah Agung Wiwekananda (Universitas Gadjah Mada, 2023)
To date, the data describing various nutritional and secondary metabolites content of Lablab beans is incomplete. Therefore, this study evaluated the nutritional value, secondary metabolites, and antioxidant activity of three different variants of Lablab beans, i.e., brown, black, and cream beans. The results showed that the brown Lablab beans had outperformed other variants according to their nutritional value and flavonoid content with outstanding DPPH scavenging activity. However, the black beans also showed good bioactive contents through their total phenolic percentage with decent reducing activity via the FRAP assay. Those who are keen in developing functional food from Lablab beans should consider this data as a reference.